Conflict And Consensus in Fiqh Siyasah: The Practice of Islamic Law Across Various Cultures - Mulia, Muji; Zulfatmi, Zulfatmi; Khalil, Zakki Fuad; Kurniawan, Cecep Soleh; Rizki, Darlin (SCAD Independent, 2024)
The Acehnese in various regions face the challenge of reconciling Islamic teachings with local cultural realities. Addressing religion-based conflicts is particularly difficult because local cultures often contain norms and traditions that differ from Islamic teachings. This research aims to explore how the dynamics of conflict and consensus in fiqh siyasah shape the cultural life of the Acehnese. The research consolidates previous studies using a Systematic Literature Review (SLR). The findings indicate that the practice of siyasah jurisprudence is highly relevant in fostering social solidarity and tolerance. Local traditions and customs hold deep significance for the Acehnese community; however, conflicts often arise due to differences in approaches and interpretations of Islamic law, leading to tension, mistrust, and suspicion among individuals. Presently, religion-based conflicts are mediated solely by Sharia courts, raising concerns as the prevailing consensus favors a socio-cultural approach. Such resolution methods generate diverse perspectives, as decisions made by customary institutions may not endure in a dynamic socio-cultural context. Although the Acehnese community firmly adheres to a culture-based approach, religious issues remain difficult to compromise. These findings imply a need for harmonization between local customs and interpretations of Islamic law to reduce conflict.